2021
DOI: 10.1016/j.jstrokecerebrovasdis.2021.105715
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Stroke Outcomes in Atrial Fibrillation Patients Treated with Rivaroxaban and Warfarin

Abstract: Objectives: In a previous real-world study, rivaroxaban reduced the risk of stroke overall and severe stroke compared with warfarin in patients with nonvalvular atrial fibrillation (NVAF). The aim of this study was to assess the reproducibility in a different database of our previously observed results (Alberts M, et al. Stroke. 2020;51:549-555) on the risk of severe stroke among NVAF patients in a different population treated with rivaroxaban or warfarin. Material and Methods: This retrospective cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
2
2
Order By: Relevance
“…Furthermore, different types of stroke (e.g., large artery atherosclerosis stroke) and atrial fibrillation (e.g., valvular atrial fibrillation) should be considered to assess the specificity of clinical application of the risk score for identifying CCE in NVAF patients. (3) Some previous studies indicated that non-vitamin K antagonist oral anticoagulants may have better effect for stroke prevention than warfarin in NVAF ( 8 , 30 , 31 ), which is inconsistent with our findings. Less participants with the use of rivaroxaban are included in the present CCE patients, which may be the main cause to result in the current findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, different types of stroke (e.g., large artery atherosclerosis stroke) and atrial fibrillation (e.g., valvular atrial fibrillation) should be considered to assess the specificity of clinical application of the risk score for identifying CCE in NVAF patients. (3) Some previous studies indicated that non-vitamin K antagonist oral anticoagulants may have better effect for stroke prevention than warfarin in NVAF ( 8 , 30 , 31 ), which is inconsistent with our findings. Less participants with the use of rivaroxaban are included in the present CCE patients, which may be the main cause to result in the current findings.…”
Section: Discussioncontrasting
confidence: 99%
“…(3) Some previous studies indicated that non-vitamin K antagonist oral anticoagulants may have better effect for stroke prevention than warfarin in NVAF (8,30,31), which is inconsistent with our findings. Less participants with the use of rivaroxaban are included in the present CCE patients, which may be the main cause to result in the current findings.…”
Section: Discussioncontrasting
confidence: 99%
“…These HRU and cost reductions associated with rivaroxaban could potentially reflect differences in its clinical profile relative to warfarin based on evidence from real-world clinical practice [ 29 , 30 , 48 50 ]. In prior studies among NVAF patients with diabetes, rivaroxaban has been associated with improved clinical outcomes along with HRU benefits relative to warfarin [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we further analyzed the influence of different anticoagulant drugs on the incidence of CCE, and the results showed that our conclusions were consistent with those of previous studies, indicated that non-vitamin K antagonist oral anticoagulants may have better effect for stroke prevention than warfarin in NVAF, which provided a good inspiration for our clinical drug selection. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, we further analyzed the influence of different anticoagulant drugs on the incidence of CCE, and the results showed that our conclusions were consistent with those of previous studies, indicated that non-vitamin K antagonist oral anticoagulants may have better effect for stroke prevention than warfarin in NVAF, which provided a good inspiration for our clinical drug selection. 32,33 Although we have fully evaluated the potential clinical significance of NVAF related CCE risk scores, some limitations could be noted, and the retrospective nature of this investigation could have given rise to some biases. First, because the selected patients were all inpatients in the department of cardiology of our hospital, there is a selection bias.…”
mentioning
confidence: 99%